Assessment of aqueous leaf extract of false rubber tree (Holarrhena floribunda) on vegetative growth of three varieties of cocoa seedlings - Babalola , Eunice Adenike; Alamu, Lateef Oyewole (Journal of Pure and Applied Agriculture, 2023)
The recent challenge facing the optimum production of cocoa in Nigeria is the scarcity of rich topsoil for nursery production which often leads to poor growth and development of cocoa trees. This study therefore, assessed the effect of aqueous leaf extract of Holarrhena floribunda (G.) on the vegetative growth of three varieties of cocoa seedlings. The experiment was conducted within the Nursery Section of Cocoa Research Institute of Nigeria, Ibadan. Completely Randomized Design (CRD) was adopted with seven treatments using varied concentrations of Holarrhena floribunda (H. floribunda ) at 10, 5, 3.33 and 2.5%; Supergro, CocoBoost and control. The three cocoa varieties planted were CRIN TC1, V1; CRIN TC3, V2; and F3 Amazon, V3. Treatments were directly sprayed on the leaves of cocoa seedlings at two weeks interval starting from fourth week after seeds sprouting for 16 weeks. Data were collected at two weeks interval for sixteen weeks on numbers of leaf, plant height, stem girth and leaf area. Two way analysis of variance (ANOVA) was used to analyze the collected data at 5% level of significance. The result showed that Treatment 1 (10% concentration of H. floribunda) significantly (p<0.05) enhanced the vegetative growth of the three varieties of cocoa seedlings, especially on the number of leaves (16.11) and stem girth (0.98 cm). The outcome of the study showed that aqueous leaf extract of H. floribunda possesses plant macro and micro nutrients which makes it a potential plant growth enhancer for cocoa seedlings (Potassium (K) 0.70%, Calcium (Ca) 1.31%, Magnesium (Mg) 1.12%, Sodium (Na) 0.15%, Organic carbon (C) 46.0%, Nitrogen (N) 3.61%, Manganese (Mn) 0.003%, Iron (Fe) 0.07%, Copper (Cu) 0.003%,Phosporus (P) 0.10% and Zinc (Zn) 0.007%). The study recommended that aqueous leaf extract of H. floribunda be adopted as a plant growth enhancer for cocoa seedlings at nursery stage. © 2021 Department of Agricultural Sciences, AIOU